2022
DOI: 10.5489/cuaj.7821
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of human papillomavirus positivity with tumor characteristics in an Irish penile cancer population

Abstract: Introduction: Penile cancer is a rare malignancy, with a European-wide annual incidence rate of 1/100 000 males. Approximately one-third of cases are attributable to human papillomavirus (HPV) infection. p16INK4a is a recognized surrogate marker for HPV infection in penile cancer. University Hospital Waterford (UHW) is the national referral center for penile cancer in Ireland. We report the prevalence of HPV infection and histological characteristics of an Irish penile cancer cohort using p16INK4a as a surroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Among the studies included in our analysis, a total of twenty-nine studies reported HPV status. Out of these, eighteen studies employed the polymerase chain reaction (PCR) method for HPV detection [13,15,19,20,22,23,[25][26][27][28][31][32][33][35][36][37][38][39], six studies utilized in situ hybridization (ISH) [4,21,24,29,34,40], and four studies did not specify the method used for HPV detection [41][42][43][44]. Additionally, one study employed a Quantus fluorometer for the detection of HPV nucleic acid [30].…”
Section: Hpv Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies included in our analysis, a total of twenty-nine studies reported HPV status. Out of these, eighteen studies employed the polymerase chain reaction (PCR) method for HPV detection [13,15,19,20,22,23,[25][26][27][28][31][32][33][35][36][37][38][39], six studies utilized in situ hybridization (ISH) [4,21,24,29,34,40], and four studies did not specify the method used for HPV detection [41][42][43][44]. Additionally, one study employed a Quantus fluorometer for the detection of HPV nucleic acid [30].…”
Section: Hpv Detection Methodsmentioning
confidence: 99%
“…Among the studies included in our analysis, Brazil and the United States both had the highest number of studies, with each country contributing eight studies (refer to Figure 2 for details). Fourteen studies reported on both HPV and p16 IHC status [4,13,[19][20][21][22][23][24][25][26][27][28][29][30], fifteen studies [15,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] focused solely on HPV, and five studies [45][46][47][48][49] reported only on p16 status. For a summary of HPV and p16 positivity across the 34 included studies, please refer to Table 1 and Supplemental Table S2.…”
Section: Study Characteristicsmentioning
confidence: 99%